Utilization of social network sites as a tool for employment seeking process by individuals in human resources management context - Sander, Tom Heinrich (Latvijas Universitāte, 2016)
Tehnoloģiju inovācijas un piemērotu kandidātu trūkums brīvajām vakancēm ir iemesls izpētīt tiešsaistes sociālos tīklus (SNS). Promocijas darba rezultātā noteikts, ka sociālajiem tīkliem ir potenciāls, lai tos izmantotu darba meklēšanas procesā. SNS mērķi un cilvēku mērķi to izmantošanai ietekmē sociālo tīklu izmantošanu un mehānismus. Mainīgie „uzticēšanās”, „apmaiņa” un „atbalsts” ir SNS mehānisma galvenie elementi. Sociālajos tīklos privātums un uzticēšanās ir zemā līmenī un tos pamatā izmato informācijas apmaiņai. Korelācijai starp SNS izmantošanu un darba meklēšanas procesu ir zemi korelācijas koeficienti. Atslēgas vārdi: sociālās tīklošanas vietnes, sociālais kapitāls, darba meklēšanas process, cilvēkresursu vadība.

Tom Sanders dissertation “Utilization of social network sites as a tool for employment seeking process by individuals in human resources management context” is devoted to the role and tasks of social network sites (SNSs) under consideration of the employment seeking process. The innovation of the technology and the gap of suitable candidates for open positions is the reason to research SNSs. The labour market is changing e.g. demographic changes is the reason to investigate new tools and channels to contact employees and to identify suitable candidates quickly and easily on the most economical basis. Under these circumstances the human resources management (HRM) is assuming increasing importance. The recruiting process especially influences the competiveness and success of a company. SNSs can give access to potential candidates. The various stakeholders of SNSs have different objectives, interests and benefits with SNSs. The private SNSs and business SNSs have different purposes. The operations of the mechanism in SNSs have been explained with social capital theory to provide recommendations to organisations. The research tests the theory to find out the usefulness of social capital theory to identify new mechanisms on SNSs and provide a framework to research SNSs and the employment seeking process. Based on the literature review and theoretical framework qualitative interviews have been carried out. The results of the interviews define variables for the further empirical research and provide a deeper insight. The data of the quantitative survey with more than 900 participants has been analysed with different statistic tools. The practical aim of the dissertation is to clarify the use of SNSs. The management needs information about SNSs that HRM can use SNSs as a management tool for the recruiting process and understands the mechanism and operations on SNSs which gives a strategic advantage to the organisation. The result of the dissertation is that SNSs have the potential to be used for the employment seeking process. The purpose of the SNS and objectives of the members influence the use and mechanism of SNS. The variable ”trust”, “exchange” and “support” are key elements for the mechanism of SNSs. Privacy and trust is on a low level on SNSs and they are mainly used to exchange information. The correlation between the use of SNSs with the employment seeking process has weak correlation coefficients.
Tiešsaistes sociālo tīklu izmantošana kā indivīdu darba meklēšanas procesa līdzeklis cilvēkresursu vadības kontekstā: promocijas darbs
Keywords: Vadībzinātne; Biznesa vadība; Management; Business management